2007
DOI: 10.1002/ijc.23224
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of two 10B‐compounds in liver metastases of colorectal adenocarcinoma for extracorporeal irradiation with boron neutron capture therapy (EORTC Trial 11001)

Abstract: Disseminated metastases of colorectal cancer in liver are incurable. The trial EORTC 11001 investigates whether autotransplantation after extracorporeal irradiation of the liver by boron neutron capture therapy (BNCT) might become a curative treatment option because of selective uptake of the compounds sodium mercaptoundecahydro-closo-dodecaborate (BSH) or L-para-boronophenylalanine (BPA). BSH (50 mg/kg bw) or BPA (100 mg/kg bw) were infused into patients who subsequently underwent resection of hepatic metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 45 publications
1
40
0
1
Order By: Relevance
“…After comparing the uptake of these two compounds in liver metastases derived from colorectal cancer, a higher boron concentration in the liver metastases was found after BPA administration than after BSH injection. [16] Hence, the choice of compound does not always depend on the boron content of the molecule and often both compounds are combined. [17] No other boron-delivery agent has reached phase I biodistribution studies to date, even though BSH and BPA efficiencies are not always sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…After comparing the uptake of these two compounds in liver metastases derived from colorectal cancer, a higher boron concentration in the liver metastases was found after BPA administration than after BSH injection. [16] Hence, the choice of compound does not always depend on the boron content of the molecule and often both compounds are combined. [17] No other boron-delivery agent has reached phase I biodistribution studies to date, even though BSH and BPA efficiencies are not always sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was no evidence of tissue damage in any organs assayed in Figure 4, either in the presence or absence of the external magnetic field. Nonetheless, all these promising results suggest that the delivery system can be potentially applied to the treatment of not only brain tumors, but also for other kinds of cancers through BNCT [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a Finnish research group recently reported that a patient with recurrent head and neck tumors showed an excellent response to BNCT treatments [7]. Lung and liver tumors have also been investigated as potential candidates for BNCT [8,9]. Selective accumulation of boron in the tumor cells produces a substantial therapy ratio during BNCT.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical interest in BNCT has also been focused on high-grade gliomas (Chanana et al, 1999), as well as the treatment of malignant meningiomas (Tamura et al, 2006) and cutaneous melanomas (Mishima & Kondoh, 2000). More recently, interest has been extended to other forms of neoplasms such as head-neck cancers (Kankaanranta et al, 2007), liver (Wittig et al, 2008a) and lung tumours , as well as undifferentiated thyroid cancers (Dagrosa et al, 2007). The treatment is binary and is carried out following two distinct phases.…”
Section: Principles Of Boron Neutron Capture Therapymentioning
confidence: 99%